Measurement of iron, magnesium and chromium concentrations in the saliva of the patients undergoing fixed orthodontic treatment - Valiollah Arash; Mehdi Pouramir; Mahmoud Hajiahmadi; Somayeh Mirzafarjooyan (Babol University of Medical Sciences, 2012)
Introduction: Stainless steel alloy used in orthodontics has elements such as iron - magnesium and chromium , which may be released due to corrosion in the mouth . The aim of this study was to evaluate the changes of these elements in the saliva of patients undergoing fixed orthodontic treatment. Methods: In a clinical study with simple non- random sampling , 1ml saliva of 11 patients (7 females and 4 males ) who needed fixed orthodontic treatment and had no restorations or crowns were collected. During the fixed orthodontic treatment at successive times ( a day, a week, a month , two months and six months ), 1 ml of saliva was collected and evaluated for the amount of iron ( spectrophotometry), chromium ( atomic absorption), and magnesium ( spectrophotometry ). Bracket , band and wire used in all patients were stainless steel alloy and were manufactured by Dentaurum Company. After sample collection , the data analysis was performed with " Azeri- 5" and "10SPSS" software and repeated measures test. Results: The mean concentration of iron 66.326±0.541, chromium 0.483±0.324 and magnesium 0.552±293 decreased during the study but these results were not statistical y significant (p>0.05). Conclusions: Iron , chromium and magnesium concentration do not exceed the standard limits in saliva during orthodontic treatment.